KARAKTERISTIK LINGKUNGAN KAWASAN PERMUKIMAN NELAYAN DI WILAYAH PESISIR DESA BOTUBARANI - Fendy Faizal Gobel; Yohanes P Erick A; Amelia Usman (JAMBURA Journal of Architecture, 2023)
The coastal area is home to the fishing community of Botubarani Village, where the community depends on marine catches as their source of livelihood. Understanding the environmental characteristics of areas that serve fishermen is crucial for formulating policies and strategies for sustainable development. The purpose of this research is to find the characteristics of the physical environment that serves fishermen, the characteristics of the social environment that involves fishermen, and the characteristics of the natural environment related to fishermen. These three objectives were chosen because they are representative in the context of involving fishermen and have significant environmental challenges. This research uses a descriptive methodology with a rationalistic approach. Data collection was carried out using the method of direct observation of fishermen to gain an in-depth understanding of the characteristics of the physical environment, spatial planning, and daily life of fishermen, and conducting interviews with fishing communities and village governments to gain an understanding of their rational views of the environmental characteristics of village fishermen. Botubarani.